RWEQ wind erosion predictions for variable soil roughness conditions - de Oro, Laura Andrea; Colazo, Juan Cruz; Buschiazzo, Daniel Eduardo (2017)
The soil surface is a main factor in all wind erosion prediction models including the Revised Wind Erosion Equation (RWEQ). The objetive of this study was to test the erodibility of two typical soils of the semiarid Argentinean Pampas under different tillage conditions (compared to a flat surface)at three wind velocities using a wind tunnel and to evaluate the performance of the RWEQ model.